Desiccation-driven senescence in the resurrection plant Xerophyta schlechteri (Baker) N.L. Menezes - Radermacher, Astrid Lillie (Department of Molecular and Cell Biology, 2020)
Drought-induced senescence is a degenerative process that involves the degradation of cellular metabolites and photosynthetic pigments and uncontrolled dismantling of cellular membranes and organelles. Angiosperm resurrection plants display vegetative desiccation tolerance and avoid drought-induced senescence in most of their tissues. Developmentally older tissues, however, fail to recover during rehydration and ultimately senesce. Comparison of the desiccation-associated responses of older senescent tissues (ST) with non-senescent tissues (NST) will allow for understanding of mechanisms promoting senescence in the former and prevention of senescence in the latter. In the monocotyledonous resurrection plant Xerophyta schlechteri (Baker) N.L.Menezes, leaf tips senesce following desiccation, whereas the rest of the leaf blade survives. This study characterised structural, metabolic and transcriptional changes in ST and NST at varying water contents during desiccation and rehydration. Light and transmission electron microscopy was used to follow anatomical and subcellular responses, and metabolic differences were studied using gas chromatography-mass spectrometry and colorimetric metabolite assays. These results show that drying below 35% relative water content (0.7 gH2O/g dry mass) in ST resulted in the initiation of age-related senescence hallmarks and that these tissues continue this process after rehydration. Analysis of the transcriptome was done using RNA-Seq, which was subject to differential expression analysis and network analysis to elucidate the potential mechanisms for senescence regulation in this species. Significantly increased transcription of senescence associated genes was observed in the air dry sampling point, indicating that initiation of cellular death occurred below 20% RWC. Network analysis based on Pearson correlation revealed a high degree of clustering of these genes, suggesting co-regulation. The majority of these genes had two enriched motifs in their upstream regions, identified as binding sites for WRKY and other transcription factors. A model integrating these observations is presented, with insights into how senescence is initiated in ST and repressed in NST.